“I take hot showers so I can practice burning in hell” A corpus analytical study of Tinder female profiles in the UK - Clara Cantos-Delgado; Carmen Maíz-Arévalo (Revista Alicantina de Estudios Ingleses)
The focus of this article is the linguistic choices made by women-seeking-men (WSM) and women-seeking-women (WSW) on Tinder profiles in the UK, which builds on prior corpus-analytical research on dating profiles (Baker 2018; Collins 2019). Data was collected through TinderBotz, a scraping tool which gathered the information publicly displayed on Tinder profiles. Then, to ensure an ethical research praxis, it assigned each profile random identification numbers that guaranteed the anonymity of the users. The corpus consists of two subcorpora (WSM.C and WSW.C) each containing 405 profiles (average number of words=20.15) from women (18-24 y.o.) based in the UK. Given that profile creation on Tinder consists of two parts (the first being semi-guided and the second part, aka the ‘about me’ section, being fully creative), each sub-corpora (WSM.C and WSW.C) was in turn divided into two parts. UK.WSM.T.P.C.1 and UK.WSW.T.P.C.1 include the semi-guided part of the profile while UK.WSM.T.P.C.2 and UK.WSW.T.P.C.2 include the ‘about me’ section). Sketch Engine was used to search for significant n-grams and keywords in both sub-corpora and chi-square tests were conducted to determine the significance of our findings. Our results showed that WSM had less elaborate profiles, mentioned physical attributes (e.g., height) and often redirected potential matches to other platforms (i.e., Instagram). Meanwhile, WSW had more creative ‘about me’ sections in which they described their identity in greater detail (e.g., leatherdyke). Overall, both groups showed similar profiles in terms of work and relationship status.